Strengthening rural livelihoods : the Impact of information and communication technologies in Asia - Grimshaw, David J., |d 1950-; Kala, Shalini; International Development Research Centre (Canada) (Ottawa [Ont.] : Practical Action Pub, International Development Research Centre, 2011)
Enthusiasm amongst international development agencies about harnessing the potential of information and communications technologies (ICTs) for development has waned as observers have recently questioned the impact and sustainability of such interventions.
Beyond technology : making information work for livelihoods / David J. Grimshaw -- Price transparency in agricultural produce markets : Sri Lanka / Sriganesh Lokanathan, Harsha de Silva and Iran Fernando -- A crop nutrient management decision support system : India / Daniel Anand Raj ... [et al.] -- LifeLines : livelihood solutions through mobile technology in India / S.M. Haider Rizvi -- Connecting to work : non-agricultural livelihood opportunities for rural wage labour in Sri Lanka / Amila Balasuriyz and Nilakshi de Silva -- Impact assessment of the e-AGRIKultura project : Philippines / Erniel B. Barrios ... [et al.] -- Evaluation of a rural information project in Ningxia, China / Nie Fengying ... [et al.] -- Beyond projects : making sense of the evidence / Jayantha Gunasekera and Ramona Miranda.
Includes bibliographical references and index.
Keywords: Communication in rural development -- Asia; Information technology -- Asia